Chronic airflow limitation and its relation to respiratory symptoms among ever-smokers and never-smokers: a cross-sectional study. Issue 1 (5th August 2020) - Toren, Kjell; Schiöler, Linus; Lindberg, Anne; Andersson, Anders; Behndig, Annelie F; Bergström, Göran; Blomberg, Anders; Caidahl, Kenneth; Engvall, Jan; Eriksson, Maria; Hamrefors, Viktor; Janson, Christer; et al.
Abstract : Background: The diagnosis of chronic obstructive pulmonary disease is based on the presence of persistent respiratory symptoms and chronic airflow limitation (CAL). CAL is based on the ratio of forced expiratory volume in 1 s to forced vital capacity (FEV1 :FVC) after bronchodilation, and FEV1 :FVC less than the fifth percentile is often used as a cut-off for CAL. The aim was to investigate if increasing percentiles of FEV1 :FVC were associated with any respiratory symptom (cough with phlegm, dyspnoea or wheezing) in a general population sample of never-smokers and ever-smokers. Methods: In a cross-sectional study comprising 15 128 adults (50–64 years), 7120 never-smokers and 8008 ever-smokers completed a respiratory questionnaire and performed FEV1 and FVC after bronchodilation. We calculated their z -scores for FEV1 :FVC and defined the fifth percentile using the Global Lung Function Initiative (GLI) reference value, GLI5 and increasing percentiles up to GLI25 . We analysed the associations between different strata of percentiles and prevalence of any respiratory symptom using multivariable logistic regression for estimation of OR. Results: Among all subjects, regardless of smoking habits, the odds of any respiratory symptom were elevated up to the GLI15–20 strata. Among never-smokers, the odds of any respiratory symptom were elevated at GLI<5 (OR 3.57, 95% CI 2.43 to 5.23) and at GLI5–10 (OR 2.57, 95% CI 1.69 to 3.91), but not at higher percentiles. Among ever-smokers, the odds of any respiratory symptom were elevated from GLI<5 (OR 4.64, 95% CI 3.79 to 5.68) up to GLI≥25 (OR 1.33, 95% CI 1.00 to 1.75). Conclusions: The association between percentages of FEV1 :FVC and respiratory symptoms differed depending on smoking history. Our results support a higher percentile cut-off for FEV1 :FVC for never-smokers and, in particular, for ever-smokers.